Private cloud computing platforms. Analysis and implementation in a Higher Education Institution - Pinhal, Nuno Miguel Correia do Novo (2013)
The constant evolution of the Internet and its increasing use and subsequent entailing to private and public activities, resulting in a strong impact on their survival, originates an emerging technology. Through cloud computing, it is possible to abstract users from the lower layers to the business, focusing only on what is most important to manage and with the advantage of being able to grow (or degrades) resources as needed. The paradigm of cloud arises from the necessity of optimization of IT resources evolving in an emergent and rapidly expanding and technology. In this regard, after a study of the most common cloud platforms and the tactic of the current implementation of the technologies applied at the Institute of Biomedical Sciences of Abel Salazar and Faculty of Pharmacy of Oporto University a proposed evolution is suggested in order adorn certain requirements in the context of cloud computing.